Reducing the PAPR of OFDM Systems by Random Variable Transformation - Taher, Montadar Abas; Singh, Mandeep Jit; Ismail, Mahamod Bin; Samad, Salina Abdul; Islam, Mohammad Tariqul (ETRI journal, 2013)
Peak power reduction techniques in orthogonal frequency division multiplexing (OFDM) has been an important subject for many researchers for over 20 years. In this letter, we propose a side‐information‐free technique that is based on the concept of random variable (RV) transformation. The suggested method transforms RVs into other RVs, aiming to reshape the constellation that will consequently produce OFDM symbols with a reduced peak‐to‐average power ratio. The proposed method has no limitation on the mapping type or the mapping order and has no significant effect on the bit error rate performance compared to other methods presented in the literature. Additionally, the computational complexity does not increase.